Does Omega‐3 supplementation increase profuse postpartum hemorrhage? A hospital‐based register study - Julia Lichtenstein; Irene Sterpu; Pelle G. Lindqvist (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Although Omega‐3 is thought to have anticoagulative properties, the potential untoward effects of Omega‐3 during pregnancy have not been investigated. No previous studies have been made to specifically assess its effect on postpartum hemorrhage (PPH). Our aim was to determine if an association exists between Omega‐3 intake during pregnancy and profuse PPH or massive PPH. Material and Methods Data on all deliveries that occurred at Karolinska University Hospital during the years 2007–2011 (n = 41 139) was collected from the medical record of Obstetrix, maternal health and delivery chart system. Women with reported Omega‐3 use in early pregnancy were considered exposed and all other as unexposed. Bivariate and adjusted multivariate analysis was performed on main outcomes. Results Omega‐3 use was associated with 25% increased odds of PPH (adjusted odds ratio (aOR) 1.25, 95% confidence interval [CI] (1.06–1.47)) and a more than doubled odds of massive PPH (aOR 2.36, 95% CI 1.26–4.44). In addition, there was a minor increase in the amount of blood loss. Although few, women on low‐dose discontinued terminated at 36th week showed no significant association to blood loss measurements. Conclusions Our observational findings showed 25% higher odds of PPH and two times higher odds of massive PPH in women who reported using Omega‐3 in early pregnancy. Our findings give some support to advocate discontinued use of Omega‐3 in late pregnancy.